ELECTRICAL PROPERTIES ANALYSIS OF IN-PLANE ZnO NANORODS GROWN BY DC-UNBALANCED MAGNETRON SPUTTERING FOR PHOTODETECTOR APPLICATION - ABIYYU KENICHI PURBAYANTO (NIM : 10214067), MUHAMMAD
We study the electrical properties of in-plane ZnO nanorods grown by DC-Unbalanced Magnetron Sputtering. As a comparison, ZnO thin film is deposited as well. Furthermore, surface morphology images and X-ray diffraction patterns show that the nanorods diameter are varying from 50 to 90 nm with hexagonal wurtzite structure. To study the electrical properties of ZnO nanorods, we perform the current-voltage (I-V) measurement using Ag as the metal contact. It shows that the dark current of ZnO nanorods is dramatically reduced leading to high photosensitivity under UV exposure. We found that the oxygen vacancy (VO) has an important role to enhance the sensitivity of ZnO nanorods. Photoluminescence spectra show that ZnO nanorods have the high density of VO compared to the thin film. This VO influences the optical bandgap, which leads to Burstein-Moss effect as revealed by UV-Vis spectroscopy. In addition, spectroscopic ellipsometry shows the excitonic screening effects due to the high distribution of VO, which acts as the localized states in the nanorods sample. We propose that the in-plane arrangement of ZnO nanorods is more effective and provides high surface-to-volume ratio that enhances the sensitivity of photodetector. Our results show the importance of in-plane ZnO nanorods structure to improve the performance of photodetector.